Penerapan Model Pembelajaran Round Table dan Rally Coach Berbantuan Media Gambar dalam Meningkatkan Hasil Belajar dan Keterampilan Communication Siswa di Kelas IV SD - Souhoka, Renny; Septory, Jekriel; Reiwuty, Paulina; Sairiltiata, Sefanya (Kamboti Journal of Education Research and Development, 2022)
This study aims to improve communication skills and student learning outcomes by applying the learning model of the Round Table and Rally Coach with the help of Picture Media to the fourth grade students of SD Negeri Wulur. The research method used in this research is (classroom action research). The type of research used in this research is classroom action research (CAR) with a qualitative descriptive approach and a quantitative descriptive approach. Qualitative descriptive research is research by searching and processing data - the data obtained do not use numbers. Based on the results of the final test of the second cycle, it showed that there was an increase in learning outcomes from the initial test showing 22.22% classical completeness, in the first cycle it reached 55% and the second cycle 100%. This shows that the application of the round table and rally coach learning models with the help of picture media has a very positive impact on learning in the classroom. In addition to student learning outcomes, the coomication ability of fourth graders at Wulur State Elementary School also increased. This can be seen in the teaching and learning process and students respond to learning well. The percentage of the implementation of learning by teachers in the first cycle reached 75% and the implementation of learning by students reached 77.89%. The percentage of the implementation of learning by teachers in the second cycle increased to 85% and the implementation of learning by students increased to 84.89%.